Hilliardiella elaeagnoides and H. oligocephala (Asteraceae, Vernonieae), two distinct species and the description of a new variety - Herman, Paul P.j. (Phytotaxa, 2022)
The two species Hilliardiella elaeagnoides and H. oligocephala were confused with each other in the past. Examination of herbarium specimens proved that they are two distinct and separate species. H. oligocephala var. besteri is newly described.